ISOLATION AND CHARACTERIZATION OF LACTIC ACID BACTERIA FROM BREAST MILK - Indrayati, Sri; Susanto, Vetra (JURNAL KATALISATOR, 2024)
Breast milk (breast milk) is one of the sources of Lactic Acid Bacteria (BAL), which functions to maintain the balance of the baby's digestive microflora. BAL derived from breast milk has high viability in the digestive tract and is more adaptive if it comes from the human body. Some BALs are also called probiotics. If Lactic Acid Bacteria Isolate is obtained from breast milk, it can be used as a probiotic candidate in the prevention of stunting and infectious diseases in children. This research applies new biotechnology to produce a food product that is healthy, contains probiotics, and is preferred by the community. The purpose of the study is to isolate and test the probiotic potential of BAL strains isolated from breast milk so that it can have the potential to be applied in the food industry. This research method is an exploratory study to obtain Lactic Acid Bacteria isolate from Breast Milk. The results of the study showed that 14 Lactic Acid Bacteria Isolate was obtained which was shown by the formation of a clear zone area around the colony. Based on the results of biochemical identification, of the 14 BAL isolates that have been successfully identified biochemically, consisting of several genera of BAL, namely Lactobacillus dan Pediococcus.